Calculation and Simulation of Aluminium Alloy Flange Reducer Cast Using Resin Sand Mold - Andi Ari Putra; Muhammad Syahid; Andi Amijoyo Mochtar (EPI International Journal of Engineering, 2021)
One of the causes of defects in casting is due to poor gating system design. In conventional casting methods, the gating system design process is carried out by trial and error to find the best design results. Computer modeling and simulation offer process design in a much faster time, and at much less cost, compared to conventional methods. The gating system design approach with a combination of well calibrated simulation software can avoid defect before casting. Casting simulation helps to visualize the phenomena of filling, molten metal solidification, and shrinkage porosity. The resulting casting simulation can be displayed in graph variants at specific nodes with line graphs or numerical numbers manually. This study discusses the simulation of casting a flange reducer from aluminum alloy material using a resin sand mold. The initial dimensions of the gating system used are sprue of 14.5 x 8.4 x 180 mm, runner 147 x 10 x 5.5 mm, ingate 80 x 10 x 5.5 mm with a bottom gate channel system. Total of dominant porosity that occurs using the initial gating system is 65.31 % and show the undirectional solidificiation behavior. After modifying the gating system and increasing the riser size, the simulation results show directional solidification behavior starting from the thinnest part to the thickest part and ending at the riser. The shrinkage porosity can compensate with the total of porosity is 57.60 % at the riser . Modification of the channel system is required to obtain a sound casting or porosity free.